1990
DOI: 10.1111/j.1749-6632.1990.tb24309.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Diagnosis of β‐Thalassemia in Sardiniaa

Abstract: This paper reviews the characteristics and the results of 15 years of experience with a preventive program, based on carrier screening and prenatal diagnosis, designed to control thalassemia major in the Sardinian population. The education of the population about thalassemia and the modalities for its prevention was accomplished via the mass media. Carrier screening was carried out voluntarily on couples of child-bearing age. Prenatal diagnosis was initially carried out by fetal blood analysis; since 1983, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 27 publications
0
29
1
2
Order By: Relevance
“…All these possible misunderstandings are in contrast with data from this study and enquiries made among populations at risk showing that at least 80% of the well-informed multi-ethnic people in The Netherlands would choose for counseling and prevention in case of increased risk [18]. Additionally, many studies in other European, (North- and South) American and Islamic countries have shown a decrease in the number of affected children after proper information and counseling [19,20,21,22,23,24,25,26]. …”
Section: Discussioncontrasting
confidence: 46%
“…All these possible misunderstandings are in contrast with data from this study and enquiries made among populations at risk showing that at least 80% of the well-informed multi-ethnic people in The Netherlands would choose for counseling and prevention in case of increased risk [18]. Additionally, many studies in other European, (North- and South) American and Islamic countries have shown a decrease in the number of affected children after proper information and counseling [19,20,21,22,23,24,25,26]. …”
Section: Discussioncontrasting
confidence: 46%
“…The b + IVS-1 nucleotide 110 seems to be prevalent in the eastern part of the Mediterranean area, including Turkey [10], Lebanon [11], and Egypt [12]. On the other hand, the b 0 -39 mutation is almost exclusive to Sardinia [13]. It is also highly prevalent in Italy [14] and Spain [15] and is frequently encountered in Portugal [16,17] and Tunisia [18].…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is of particular im portance for carrier detection, genetic coun selling and prenatal diagnosis. Prevention of the disease can be achieved sucessfully by genetic counselling and prenatal diagnosis, as was shown to be the case in Sardinia, Cyprus and Greece [8][9][10], In Saudi Arabia, the P-thalassaemias, first reported in 1976, exhibit a high, but variable, prevalence in different parts of the country [11][12][13], The clinical presentation seems to resemble that reported in other populations, but the molecular defects have not yet been elucidated. In this study, we investigated twenty mutations commonly reported in the Asian, Mediterranean and Chinese popula tions, to determine the frequency of each in an attempt to identify the ethnic-group-specific alleles in the Saudi population.…”
Section: Introductionmentioning
confidence: 99%